Pengaruh Komitmen dan Kompetensi terhadap Kinerja Karyawan Kantor Kesyahbandaran dan Otoritas Pelabuhan Cilacap - Hari Sucahyowati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Akademi Maritim Nusantara Cilacap, 2020)
This research purposes to examine the effect of commitment and competency toward employees’ performance. The samples of this research are 60 employees at Kantor Kesyahbandaran dan Otoritas Pelabuhan Cilacap. The sampling technique that will be used is census technique using Structural Equation Modeling (SEM) with Pertial Least Square (PLS) approach. Then, the results of this research are commitment has positive effect towards employee’s performance and competency has positive effect towards employee’s performance.